Hubungan Persepsi Suami Tentang Keadaan Kesuburan Istri Pasca Persalinan Dan Dukungan Suami Untuk KB Dengan Rentang Waktu Mulai KB (Studi pada akseptor KB wanita di Kelurahan Lamper Lor Kecamatan Semarang Selatan Kota Semarang Tahun 2006) - Ritmasari, Ritmasari; Lestantyo, Daru; Dharminto, Dharminto (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2007)
Background : The main purpose of family planning program is to increase the qualities of the population with birth arrangement, decrease mother mortality rate and neonatal mortality rate, and increase the quality of family planning program itself. Different perception about woman fertility condition after gave birth and not enough support from their husband causing Pasangan Usia Subur (PUS) delay their time to use family planning method. The aim of this research is to detect the correlation between perception about woman fertility condotion after gave birth and support from their husband with the time of using family planning methodat the Lamper Lor Village, Subdistrict Semarang Selatan, Semarang City in the year at 2006.Method : This research type is explanatory research with cross sectional study. The population in this research is all women memberâ€™s of family planning program in Lamper Lor Village with the member of 536 people. The sampling obtained 82 people. Method is Simple Random Sampling proportionally. Statistic test Rank Spearman Correlation at significant level 0,05. Result : The result of this research indicates that perception about breast feeding effect is medium perception category (90,20%), perception about age with medium perception level was 50,00%. Husband support for family planning program was 52,40% at medium category. Itâ€™s concluded there was correlation between breast feeding effect perception on fertilitycondition after gave birth with range of time to use family planning method (rs=-0,324;Ï=0,003), there was no correlation between age perception on fertility condition after gave birth with duration of time family planning method (rs=-0,009; Ï=0,935), and there was no correlation between husband support in participation to family planning program with range of time to use family planning method (rs=0,175; Ï=0,117).Key words : Breast feeding, Age, Coitus frequency, Range of time to use family planningmethod